EXTENT OF UNLICENSED AND OFF-LABEL DRUG USE IN THE PEDIATRIC PRACTICE OF SMOLENSK - S.A. Rachina; A.S. Belokhvostova; L.P. Zharkova; L.V. Konovalova (Union of pediatricians of Russia, 2010)
Objectives: to determine the extent of unlicensed and off-label drugs prescriptions in one of the hospitals in Smolensk. Patients and methods: The prospective pharmacoepidemiological survey for the period from January 1 to June 30, 2006 covered children admitted to the neonatal pathology unit (NPU) (newborns aged 1-30 days), medical department No. 1 for infants (aged 1 month - 3 years), medical department No. 2 for early and middle-age children (aged 4-13 years) and medical department No. 3 for teenagers (aged 14-17 years) who were prescribed at least one drug. The unlicensed drug category included: any prescriptions of drugs not registered in Russia; adult pharmaceutical forms of registered drugs that are not permitted for use in children; incorrect use of permitted pharmaceutical forms; use of chemical substances as drugs; drugs prepared by the hospital pharmacy. Prescriptions were considered off-label in the following cases: 1. off-label use; 2. failure to follow label directions; 3. counter-indications, including age restrictions. Product directions provided by drug manufacturers and 2005 National Drug Register were used as sources of information about drugs. Results: Four hundred sixty nine patients aged 1 day to 17 years (median age of 8.9 years) were included in the survey. A total of 34% prescriptions were unlicensed and 54% off-label. Prescriptions for unlicensed drugs were written at frequency rates of 39, 31, 24 and 39%, while those for off-label drugs were at 70, 58, 43 and 43% at NPU, medical department No. 1, medical department No. 2 and medical department No. 3 respectively. The most common category of unlicensed use was the administration of drugs manufactured by the local pharmacy (73%), followed by the use of adult pharmaceutical forms not permitted for use in children (14%). The most common reason for off-label prescriptions was off-label use (54%); failure to follow label directions and age restrictions in 33% and 12% of cases, respectively. Conclusion: The practice of off-label and unlicensed drug use was quite common in hospitalized children in Smolensk especially in neonatal wards. These findings highlight the shortage of clinical data on the use of drugs in pediatrics as well as the need to set up clinical trials in children, education programs for pediatricians and more active implementation of treatment standards and protocols. Key words: madications, unlicensed drug, off-label drug, children. (Pediatric Pharmacology. - 2010; 7(4):56-60)